Tracking the variability of the western Pacific warm pool heat content over 1980–2020 - Jin, Liang; Liu, Chunlei; Cao, Ning; Liao, Xiaoqing; Xue, Yufeng; Bao, Ruijuan; Fan, Lingli; Zhu, Lingjing; Su, Qianye; Yang, Ke; Zheng, Rong; Chang, Shujie; et al. (Frontiers in Earth Science, 2024)
The western Pacific warm pool (WPWP) is a major thermal driver of atmospheric deep convection and global atmospheric circulation in the tropics, and changes in its ocean heat content (OHC) affect the local and global climates. Four state-of-the-art ocean reanalyses and one objective analysis were used to study the variations in the WPWP OHC, ocean heat content tendency (OHCT), and ocean heat transport (OHT). The variabilities of both the OHC and OHCT integrated from 0 to 300 m are consistent between the datasets and are closely related to the El-Niño southern oscillation cycle. The integrated OHC from 0 to 2000 m shows an overall increasing trend in the WPWP. The WPWP mainly gains heat from the eastern boundary and loses heat from the northern boundary. The heat transport through the eastern boundary of the WPWP is mainly facilitated by the westward flowing south and north equatorial currents as well as the equatorial countercurrent around the depth of the thermocline, whereas the OHT at the northern boundary is mainly driven by the western boundary current of the Pacific Ocean, which shows complex flow structures.